Implementasi Tasyaruf Zakat Di Masa Pandemi COVID 19 Pada BAZNAS Kabupaten Purworejo - Waluyo Sudarmaji; Miftachuzzaman Miftachuzzaman (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2021)
The distribution of zakat has two contexts, namely distribution and utilization. In the current situation of the covid pandemic, the distribution context becomes very urgent to carry out considering that the economic condition of the community is increasingly critical. According to the Shari'a, the allocation of zakat has been regulated in the Qur'an, namely 8 asnaf (groups) as mustahik. However, in its implementation, the Purworejo Baznas Institution distributes zakat to assist the handling of victims of the COVID-19 pandemic, so it becomes a crucial issue to understand whether zakat distribution is permissible or not according to Islamic law. The purpose of this study was to determine the mechanism for distributing zakat through the social institution Baznas Purworejo in the perspective of Islamic law. This type of research is field research by collecting data in the form of field studies and literature studies. This type of research is descriptive analytic, which is a direct description of the problem of distributing zakat, presenting field facts to be analyzed from the aspect of Islamic law. The approach used is a normative approach based on the Qur'an and Hadith. The results showed that the distribution of zakat carried out by BAZNAS Purworejo to victims of covid 19 did not violate the principles of benefit and Islamic law. The groups that receive priority as recipients of zakat from BAZNAS Purworejo are the indigent, poor, amil and public facilities.